Cutting & sharpening for woodturners [ a lesson with Chris Stott - Stott, Chris (Chris Stott Videos, 1993)
Designed to help woodworkers get the best from woodturning tools, with instructions on how to sharpen a roughing gage, skew chisel, parting tools, scrapers, and more.